A GLOSSARY OF LEGAL TERMS IN A SCENARIO-BASED JUDICIAL CONTEXT - Zaman, Mochamad Nuruz; Nugraha, Reza Sukma (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
The use of English in judicial interactions has increased during court proceedings. A glossary is necessary to design bilingual usage in the context of real-life scenarios. This study is grounded in two theoretical foundations: legal terminology and an ethnographic approach. Qualitative research is employed to investigate the cases presented in the issue. Data are obtained through document analysis and interviews containing technical terms related to the field of judiciary and its scenarios. The data are analyzed using domain, componential, taxonomy, and cultural themes to implement the glossary design based on interviews with language practitioners in the judicial domain. Ten data samples are presented to consider the context, connotations, and clarity of the translations in judicial practice. The findings of this research indicate that implementing an ethnographic approach in designing a scenario-based bilingual legal terminology glossary has significant benefits in ensuring the appropriateness and accuracy of translating legal terms between Indonesian and English.